Opinions of the Nurse Managers on Recruitment of Nurses: A Qualitative Study - Tuğba Yeşilyurt; Ülkü Baykal; Nilgün Göktepe (Association of Nurse Managers, 2020)
INTRODUCTION: The aim of this study is to determine the views of the nurse managers about recruiting process of the nurses. METHODS: The study was conducted by using qualitative research method in descriptive and phenomenological design and the sample consisted of 43 nurses working in different institutions, managerial positions and having different experience and training. The study data have been collected via face- to- face interviews with semi-structured individual in-depth interview forms prepared by scanning the literature and evaluated with the content analysis method. RESULTS: In line with the research questions, the views of the executive nurses were addressed as 'recruitment criteria', 'recruitment process' and 'problems experienced in the recruitment process' as three main themes and subthemes of these main themes. The criteria that the nurse managers take into consideration in recruitment were determined as personal characteristics, training, experience and competence in the field. The process of recruiting nurses takes place in the form of central assignment in public institutions, the managers of institutions aren't active in this process, and in private hospitals, the human resources unit is active in the process of recruiting nurses and nurse managers are engaged in this process, especially during the decision-making process of recruiting nurses. The problems in the recruitment process have been revealed as lack of budget, competition with other institutions, difficulty in finding a competent nurse, incompetence due to low level of professional education and problems related to additional recruitment process experienced in the public hospitals were identified. DISCUSSION AND CONCLUSION: The results show that the planned and effective recruitment process is important for the recruitment of qualified and appropriate nurses, as well as the creation of a selection/placement system in public hospitals that takes into account the individual and professional qualifications of the candidate.